The opportunities and challenges of platformisation and the gig economy for young emerging Amapiano music creators in South Africa - Kgwete, David Moemedi (Rhodes University, 2026)
In South Africa, the Amapiano music genre has seen a rapid rise, propelled by its unique sound and the accessibility of online platforms for distribution and promotion. However, the dynamics of platformatisation and the gig economy present a complex environment for emerging Amapiano artistes. These musicians must navigate issues such as algorithmic (in)visibility, monetisation challenges, digital music piracy, and the precarious nature of gig-based work. This thesis explores the ways in which young South African Amapiano musicians utilise digital platforms to generate income amid high unemployment, navigate the complex and shifting dynamics of the gig economy, and evaluate the challenges that young Amapiano music creators face in their artistic journey as platform workers as well as the emotional labour that these Amapiano music creators face in their creative work. The study employed qualitative research methodology, using semi-structured and go-along interviews to collect data from twelve participants (young South African Amapiano music creators). Drawing from the diffusion of innovation theory and aspects of capital theory, the study reveals how digital platforms and gig-based opportunities influence the career trajectories of young Amapiano musicians in South Africa, as well as the challenges and constraints inherent in this space. The findings reveal that digital platforms are a huge stepping stone for South African music creators in releasing their music on the platforms, allowing them to get recognised and called for live physical performances. In addition, live physical performances have been acknowledged as the most reliable method to generate income. However, getting these live physical performances is not that easy; artistes sometimes get them through recommendations from friends. The gig economy has also been acknowledged as an ecosystem that can facilitate digital work such as beat-selling businesses, resulting in the accumulation of revenue. However, South African music creators continue to face challenges of digital music piracy, which does not seem to have a prevention or mitigation strategy. Moreover, the gig economy remains precarious for these young Amapiano music creators since digital distribution services also appear to charge artistes that are subscribed to them an extra annual fee, which young independent artistes do not seem to have the financial resources to keep up with, resulting in switching between services. South African music creators see the music industry as a 24/7 commitment, resulting in artistic growth and improved creative values. In addition, seeing the music industry as a 24/7 commitment often results in artistes facing frustrations and emotional fatigue due to the music industry pressure of keeping up with relevancy. Recommendations include artistes building relationships with concert promoters and getting booking agencies to assist in getting more live physical performances to enhance more revenue accumulation. Furthermore, young musicians could put more commitment into extending their knowledge on how to make platforms such as BeatStars and SouldClick more profitable.
Keywords: Musicians--South Africa (http://id.loc.gov/authorities/subjects/sh85089027); Musicians--South Africa (http://id.loc.gov/authorities/subjects/sh85089027); Journalism and Media Studies; Platformisation (https://www.wikidata.org/wiki/Q134290365); Amapiano (https://www.wikidata.org/wiki/Q85741139)